Financial Statements : Analysis and Reporting - Lessambo, Felix I (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Through a mixture of concepts and examples, this book demystifies the variety of elements of financial accounting and uncovers the need-to-know information for certification in this field. This book covers the two aspects of financial statement analysis, namely quantitative and non-quantitative analysis. Concluding with helpful case studies, the book will appeal to students and academics of financial accounting.
Part 1. Overview of Financial Statements and the Statement of Position -- Chapter 1. Overview of Financial Statements -- Chapter 2. Cash and Cash Equivalents -- Chapter 3. Short-Term Assets: Inventories -- Chapter 4. Account Receivables -- Chapter 5. Pre-Paid Expenses, Unearned Income and Other Current Assets -- Chapter 6. Short-Term Liabilities and Working Capital -- Chapter 7. Long-Term Assets: Plant, Property and Equipment -- Chapter 8. Long Term Assets: Intangibles -- Chapter 9. Long-Term Liabilities: Leases -- Chapter 10. Long-Term Liabilities: Pension and Post-Retirement Liabilities -- Chapter 11. Shareholders' Equity -- Part 2. The Statement of Income -- Chapter 12. Analysis of the Statement of Income -- Chapter 13. Other Comprehensive Income -- Chapter 14. The Sub-Statement of Retained Earnings -- Chapter 15. The Computation of the Taxable Income -- Part 3. The Statement of Cash Flows and Financial Ratios -- Chapter 16. Analysis of the Statements of Cash Flows -- Chapter 17. Financial Ratios Analysis -- Part 4. Pro-Forma Financial Statements -- Chapter 18. Forecasting Financial Statements' Analysis -- Part 5. Consolidated Financial Statements -- Chapter 19. Foreign Currency Accounting -- Chapter 20. Consolidated Financial Statements -- Chapter 21. Segment and Intermediary Financial Statements -- Chapter 22. IFRS and GAAP -- Part 6. Case Study -- Chapter 23. Apple and Microsoft Case Study .
Description based on publisher-supplied MARC data.
Keywords: Accounting; Financial Accounting